2021
DOI: 10.2147/cmar.s305179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of miR-183-3p and miR-182-5p in NSCLC and Their Correlation

Abstract: Purpose Accumulating evidence has indicated that dysregulated microRNAs (miRNAs) are involved in cancer progression. In this study, we evaluated the clinicopathologic significance of miR-183-3p and miR-182-5p, and the role of miR-183-3p in non-small-cell lung cancer (NSCLC) progression. Patients and Methods Seventy-six NSCLC patients from Beijing Chest Hospital were included. The expression of miR-183-3p and miR-182-5p was evaluated by real-time quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Interestingly, we found that among the 76 enrolled patients, the miR-9-5p expression in normal lung tissues of smokers was higher than that of non-smokers ( Figure 1D ). It is worth noting that we also found miR-182-5p and miR-183-3p were elevated in normal lung tissue of smokers previously ( 21 ). Meanwhile, the results of TCGA bioinformatics analysis showed that the miR-9-5p level in NSCLC tumor tissues of smokers was significantly higher than that of non-smokers ( Figure 4D ).…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, we found that among the 76 enrolled patients, the miR-9-5p expression in normal lung tissues of smokers was higher than that of non-smokers ( Figure 1D ). It is worth noting that we also found miR-182-5p and miR-183-3p were elevated in normal lung tissue of smokers previously ( 21 ). Meanwhile, the results of TCGA bioinformatics analysis showed that the miR-9-5p level in NSCLC tumor tissues of smokers was significantly higher than that of non-smokers ( Figure 4D ).…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, we proved that hsa_circ_0003176 regulated RBM5 expression via sponging miR-182-5p. Zhang et al showed that miR-182-5p was significantly increased in NSCLC tumor tissues and was correlated with tumor size and cell proliferation, suggesting that miR-182-5p played an oncogenic role in NSCLC [ 34 ]. Yang et al found that miR-182-5p was upregulated in the NSCLC tissues and promoted the NSCLC metastasis and epithelial-mesenchymal transition (EMT) by regulating EPAS1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are ubiquitous small non coding RNAs, ranging from 19–24 nucleotides in length. 5 There is an association between aberrant miRNA expression and the diagnosis and prognosis of cancer. 6 MiRNAs regulate the growth and proliferation of immune and stromal cells in the tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%